Disagreement in partners' reports of financial difficulty - Robert Breunig; Deborah A. Cobb-Clark; Xiaodong Gong; Daniella Venn (Institute for the Study of Labor (IZA), 2005)
We use unique data in which both partners report about household finances to demonstrate that there is often disagreement about whether the household has experienced financial difficulty in the past year. Four alternative explanations for this disagreement are tested using the data. The results indicate that disagreement may be related to the severity of the underlying material hardship rather than to gender differences, information asymmetries, or individual (as opposed to household) views of financial difficulty. This implies that standard surveys which collect information about the household's financial position from a representative individual may fail to completely characterize the nature of material hardship.
Keywords: C42; D14; I31; 330; household finances; survey methodology; material hardship; Familienökonomik; Lebenshaltungskosten; Haushaltseinkommen; Schätzung; Australien